Ein lokaler Grenzwertsatz für die Dichtefunktionen - Survila, P. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Сурвила. Одна локальная предельная теорема для плотностей P. Survila. Viena ribinė lokalinė teorema tankiams